1998
DOI: 10.1080/07435809809135527
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibodies in autoimmune thyroid disorders

Abstract: Different antibodies against both organ- and non-organ-specific autoantigens have been found in patients with autoimmune thyroid diseases. The aim of our study was to evaluate the presence of antineutrophil cytoplasmic antibodies (ANCA) in sera of patients affected by Graves' disease (GD) and Hashimoto's thyroiditis (HT). These antibodies were investigated by indirect immunofluorescence; the reactivity against myeloperoxidase and lactoferrin was assessed by ELISA. ANCA were detected by immunofluorescence in 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Although it was reported that aspecific (atypical) ANCAs were detected by immunofluorescence in some patients with Graves' disease [24,25], MPO-ANCA assessed by ELISA may not appear in untreated patients with Graves' disease [14, 24,25]. There may be a specific reason why the anti-thyroid drug itself, especially PTU, can induce MPO-ANCA and ANCA-associated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was reported that aspecific (atypical) ANCAs were detected by immunofluorescence in some patients with Graves' disease [24,25], MPO-ANCA assessed by ELISA may not appear in untreated patients with Graves' disease [14, 24,25]. There may be a specific reason why the anti-thyroid drug itself, especially PTU, can induce MPO-ANCA and ANCA-associated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also reported a significantly higher rate of ANCA positivity for patients under PTU treatment when compared to those receiving carbimazole. Another study investigating ANCA frequency with IFA in autoimmune thyroid diseases reported ANCA positivity in 28.5% of patients with Graves' disease and in 9% of those with Hashimoto's disease [32]. Although no significant difference was detected in overall ANCA positivity between the two groups in our study (P = 0.13), p-ANCA and mpo-ANCA positivity had a significantly higher frequency in the on-treatment group (P = 0.04 and P = 0.01, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…High ANCA titers have been observed in patients' serum samples obtained before treatment in studies with Graves' disease patients, which has been associated with the nature of the disease [3,32,34]. Other studies have reported marked decreases in ANCA levels with MMI treatment.…”
Section: Discussionmentioning
confidence: 97%
“…9,10 Unfortunately, good longitudinal studies assessing baseline prevalence of the various antibody species and conversion rates after thioamide exposure are lacking. [11][12][13][14] Indeed, there are conflicting data on the prevalence of ANCAs before thioamide initiation causing some to attribute the ANCAs to the autoimmune thyroid disease state. 6 The occurrence of ANCAs with other medications, including hydralazine, minocycline, and sulfasalazine, supports thioamide causality 15,16 as does ANCA occurrence in normal cats after propylthiouracil treatment 17 and in nonimmune-mediated disease and multinodular goiter, albeit with lower titers than in Graves disease.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical perinuclear-ANCA staining in which the immunofluorescence is more homogeneously distributed has been described. 7,11,15,30,31 Often, the enzyme-linked immunosorbent assay is negative for myeloperoxidase. Antilactoferrin and antielastase antibodies account for many atypical ANCA results, especially when drug-associated.…”
Section: Discussionmentioning
confidence: 99%